Effects of different light conditions on repair of UV-B-induced damage in carpospores of Chondrus ocellatus Holm - 鞠青 肖慧 王悠 唐学玺 (Chinese journal of oceanology and limnology, 2015)
We evaluated the effects of ultraviolet-B （UV-B） radiation and different light conditions on the repair of UV-B-induced damage in carpospores of Chondrus ocellatus Holm （Rhodophyta） in laboratory experiments. Carpospores were treated daily with different doses of UV-B radiation for 48 days, when vertical branches had formed in all treatments; after each daily treatment, the carpospores were subjected to photosynthetically active radiation （PAR）, darkness, red light, or blue light during a 2-h repair stage. Carpospore diameters were measured every 4 days. We measured the growth and cellular contents of cyclobutane pyrimidine dimers （CPDs）, chlorophyll a, phycoerythrin, and UV-B-absorbing mycosporine-like amino acids （MAAs） in carpospores on Day 48. Low doses of UV-B radiation （36 and 72 J/m2） accelerated the growth of C. ocellatus. However, as the amount of UV-B radiation increased, the growth rate decreased and morphological changes occurred. UV-B radiation significant damaged DNA and photosynthetic pigments and induced three kind of MAAs, palythine, asterina-330, and shinorine. PAR conditions were best for repairing UV-B-induced damage. Darkness promoted the activity of the DNA dark- repair mechanism. Red light enhanced phycoerythrin synthesis but inhibited light repair of DNA. Although blue light, increased the activity of DNA photolyase, greatly improving remediation efficiency, the growth and development of C. ocellatus earpospores were slower than in other light treatments.